Effect of Physical State on Pain Mediated Through Emotional Health in Rheumatoid Arthritis. Issue 9 (8th October 2018) - Nakagami, Yukako; Sugihara, Genichi; Takei, Nori; Fujii, Takao; Hashimoto, Motomu; Murakami, Kosaku; Furu, Moritoshi; Ito, Hiromu; Uda, Miyabi; Torii, Mie; Nin, Kazuko; Murai, Toshiya; et al.
Abstract : Objective: Pain is one of the main symptoms of patients with rheumatoid arthritis (RA). Pain in RA is caused by specific physical changes, such as joint destruction, and is therefore used as a disease activity marker. Although pain can also be influenced by emotional factors, neither the effect of emotional health nor the indirect effect of the physical state mediated by emotional health on pain has been quantified. Methods: A total of 548 patients with RA participated. Emotional health was assessed using the Hospital Anxiety and Depression Scale (HADS). Measures routinely used in practice were used to evaluate the physical state and pain. To quantify the effects of the physical state on emotional health, and the effects of both physical and emotional health on pain, we used structural equation modeling, with emotional health, physical state, and pain as latent variables. Results: The prevalence of anxiety and depression (HADS score ≥8 for each) among patients with RA was 18.7% and 29.4%, respectively. Emotional health was significantly influenced by the physical state (β = 0.21). Pain was affected by physical (β = 0.54) and emotional health (β = 0.29). The effect of the physical state on pain was mediated by emotional health, with this mediation effect (β = 0.06) accounting for 10.2% of the total effect. Conclusion: The magnitude of pain in RA is determined by the mediation effect of emotional health as well as the direct physical state. Our findings suggest that emotional factors should be taken into account when assessing RA disease activity.